The eden ecosystem : rebuilding Libya in a global knowledge - Barrett, Michael I.; MacNeil, Alice ([London] : SAGE, 2016)
This case demonstrates key challenges and opportunities faced by Libya and other countries with large reserves of natural resources to diversify through the development of new high tech ecosystems so as to secure a future in the global knowledge economy.
Originally Published in: Barrett, M., & MacNeil, A. (2014). The Eden Ecosystem: rebuilding Libya in a global knowledge economy. Cambridge: Middle East Research Centre, University of Cambridge, Judge Business School.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Sustainable development -- Case studies; Knowledge economy -- Case studies; Libya -- Economic policy -- Case studies